Representation of the Conflict between Tradition and Modernity in the Novel Awlad Haratina by Naguib Mahfudz: A Sociological Study of Literature - Satrya Yudha Prawira, (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the portrayal of the conflict between tradition and modernity in NaguibMahfouz’s novel Awlad Haratina. In this work, Mahfouz portrays the life of a society marked bytensions between traditional values rooted in religion and culture and the emergence of modern ideasinfluenced by the development of science and social change. This study employs the Sociology ofLiterature approach proposed by René Wellek and Austin Warren, which divides the analysis intothree aspects: the sociology of the author, the sociology of the literary work, and the sociology of thereader. This research focuses on the sociology of the literary work using a qualitative method anddescriptive analysis. The purpose of this study is to reveal how the conflict between tradition andmodernity is represented through characters, events, and social situations in the novel. The resultsshow that the tension between traditional values and modern ideas is represented through characterswho symbolize the power of tradition as well as characters who bring rational and scientific ideas.This conflict reflects the dynamics of social and intellectual change within society. Through this study,it is expected that readers will better understand the social meanings contained in the novel as well asthe reflection of changing values in society.